Evaluation of peripheral lymphadenopathy by fine needle aspiration cytology: a one year study at tertiary centre - Shah, Pinal Chintan; Patel, Chandni B.; Bhagat, Vasudha; Modi, Heta (International Journal of Research in Medical Sciences, 2016)
Background: Lymphadenopathy is common presenting features in various non-neoplastic and neoplastic lesions. Fine needle aspiration cytology (FNAC) is simple, quick, inexpensive and minimally invasive technique that can be used as an outpatient procedure to diagnose them. The present study was undertaken to assess the various causes of lymphadenopathy through FNAC, and to see the distribution of lesions with respect to age and gender. To assess the diagnostic accuracy of lymph node ﬁne needle aspiration (FNA) cytology in various non-neoplastic and neoplastic conditions. Methods: Total 555 cases of the lymph node FNAC were studied from January 2014 to December 2014 in Cytopathology department of Government Medical College, Surat .The cytomorphologic features seen in the aspirates were analyzed and correlated with their etiology. Results: In this study 555 cases of cervical lymphadenopathy were analysed. The age of the patients ranged from 5 months to 90 years of which 60.2% were males and 39.8% were females. Maximum numbers of cases 147(26.4%) were in the age group of 21- 30 years. The most common lesion encountered was tuberculous lymphadenitis 44.8% followed by metastatic tumors 31.3%, reactive lymph node 16.7%, acute lymphadenitis 5.4% and lymphoma 1.8%. Male showed predominance of metastatic carcinoma and lymphoma while chronic reactive hyperplasia and tuberculous lymphadenitis were equally distributed in both male & female. Conclusions: FNAC is safe, rapid and cost effective method in establishing the diagnosis in large number of cases of lymphadenopathy. It can differentiate a neoplastic from a non-neoplastic process and therefore influence patient management preventing patient from being subjected to unnecessary surgery.